Técnicas para la restauración y recuperación de taludes en zonas inestables de la vía Riobamba – cebadas desde el km. 1+750 hasta el km. 2+300.” - Orna Novillo, Johanna Elizabeth (2013)
The proposal to analyze a technology allowing the stabilization of the slopes from Riobamba - Cebadas route km 1+750 to km 2+300, it is based on the need to recover and restore above mentioned slopes, for this reason several factors were analyzed to establish the slopes stability like: a type of soil, topographic characteristics and problems presented by processes of erosion.